2001
DOI: 10.1002/1099-0682(200111)2001:11<2831::aid-ejic2831>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine Route Synthesis of Montmorillonites Containing Mg or Zn and Characterization by XRD, Thermal Analysis, MAS NMR, and EXAFS Spectroscopy

Abstract: EXAFS spectroscopy, combined with X‐ray powder diffraction, chemical and thermal analysis, scanning electronic microscopy, 29Si, 27Al, and 19F MAS NMR spectroscopy, are used in the structural analysis of montmorillonites, synthesised in an acidic fluoride medium. Hydrothermal synthesis performed under mild conditions (493 K, autogenous pressure) enables the formation of montmorillonite clays, containing Al and Zn or Mg in the octahedral sheet. It is shown that montmorillonites can only be synthesized in a narr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
108
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(117 citation statements)
references
References 17 publications
9
108
0
Order By: Relevance
“…11) The thermal reaction of talc and sodium fluorosilicate or lithium fluoride has been reported to obtain expandable 2:1 type silicate. 12) In addition to those commercialized products, there are several reports on the preparation of smectite-like silicates 13), 14) and intercalation compounds. 15)-18) One of the advantages of smetites as host material for the nanocomposite and hybrid materials is the variation of cation exchange capacity (CEC).…”
Section: Introductionmentioning
confidence: 99%
“…11) The thermal reaction of talc and sodium fluorosilicate or lithium fluoride has been reported to obtain expandable 2:1 type silicate. 12) In addition to those commercialized products, there are several reports on the preparation of smectite-like silicates 13), 14) and intercalation compounds. 15)-18) One of the advantages of smetites as host material for the nanocomposite and hybrid materials is the variation of cation exchange capacity (CEC).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] During the thermal consolidation of the membranes, the degree of dehydration increases with temperature and treating time.…”
Section: Discussionmentioning
confidence: 99%
“…The refined clay powders were calcined in air, and then tested by ex-situ XRD to examine the thermal stability of the crystallographic structure. around 10Å indicate closure of the interlayer space after being dried at 45°C for 48 hours, because the thickness of the octahedral clay plates is about 9.6Å [1][2][3][4][5][6][7][8][9][10][1][2][3][4][5][6][7][8][9][10][11][12][13] .…”
Section: Fig 1-3mentioning
confidence: 99%
See 1 more Smart Citation
“…The random assignment of substitutions and the first constraint that prohibits the presence of Mg-(OH) 2 -Mg pairs in the octahedral sheet are based on 1 H magic angle spinning nuclear magnetic resonance (MAS NMR) and FT-IR spectra from MMTs that show no contributions from Mg-(OH) 2 -Mg moieties and QM simulations that demonstrated that Mg 2+ substitutions are randomly distributed within the octahedral layer [35][36][37]. The second constraint, informed by the properties of synthetic MMTs [38][39][40][41], limits the substitution ratio of the edge PBC (i.e., Mg edge substitutions: total number of octahedral edge sites in the PBC) to less than 0.20, which is the maximum substitution ratio for a synthetic MMT with only octahedral substitutions. The structural characterization of synthetic MMTs with divalent cation substitution ratios greater than 0.20 revealed octahedral sheet occupancies greater than 2.00, which is indicative of an MMT structure with some trioctahedral character, and isomorphic substitutions in the tetrahedral sheet.…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 99%